(untitled) (Hekima Review, 2010)
It is a sign of the maturity of theology when it begins to analyse seriously specific themes of Christian teaching and life in relation to particular contexts. Not too long ago, “African Theology” was almost totally confined to affirming that “it is important” and that “it should be done” for the sake of African Christianity itself and the world church. How this task was to be achieved remained a dream to many early African theologians. Given the historical experience of Christianity in the continent, this is not surprising; it was an unavoidable situation, and the pioneers of African Theology must be commended for just having pointed this out. They inspired subsequent theologians with the courage to examine the propositions of the Christian faith in an African way as well as – which is the other side of the same coin – to consider elements of African spirituality on the basis of Christian teaching. In this dynamics one perceives adulthood of African Theology.